Genes Required for the Anti-fungal Activity of a Bacterial Endophyte Isolated from a Corn Landrace Grown Continuously by Subsistence Farmers Since 1000 BC - Shehata, Hanan R.; Ettinger, Cassandra L.; Eisen, Jonathan A.; Raizada, Manish N. (Frontiers in Microbiology, 2016)
Endophytes are microbes that inhabit internal plant tissues without causing disease. Some endophytes are known to combat pathogens. The corn (maize) landrace Chapalote has been grown continuously by subsistence farmers in the Americas since 1000 BC, without the use of fungicides, and the crop remains highly valued by farmers, in part for its natural tolerance to pests. We hypothesized that the pathogen tolerance of Chapalote may, in part, be due to assistance from its endophytes. We previously identified a bacterial endophyte from Chapalote seeds, Burkholderia gladioli strain 3A12, for its ability to combat a diversity of crop pathogens, including Sclerotinia homoeocarpa, the most important fungal disease of creeping bentgrass, a relative of maize used here as a model system. Strain 3A12 represents a unique opportunity to understand the anti-fungal activities of an endophyte associated with a crop variety grown by subsistence farmers since ancient times. Here, microscopy combined with Tn5-mutagenesis demonstrates that the anti-fungal mode of action of 3A12 involves flagella-dependent swarming toward its pathogen target, attachment and biofilm-mediated microcolony formation. The mutant screen revealed that YajQ, a receptor for the secondary messenger c-di-GMP, is a critical signaling system that mediates this endophytic mobility-based defense for its host. Microbes from the traditional seeds of farmers may represent a new frontier in elucidating host–microbe mutualistic interactions.